The dynamics of expertise acquisition in sport: The role of affective learning design. (January 2015) - Headrick, Jonathon; Renshaw, Ian; Davids, Keith; Pinder, Ross A.; Araújo, Duarte
Abstract: Objectives: The aim of this position paper is to discuss the role of affect in designing learning experiences to enhance expertise acquisition in sport. The design of learning environments and athlete development programmes are predicated on the successful sampling and simulation of competitive performance conditions during practice. This premise is captured by the concept of representative learning design, founded on an ecological dynamics approach to developing skill in sport, and based on the individual-environment relationship. In this paper we discuss how the effective development of expertise in sport could be enhanced by the consideration of affective constraints in the representative design of learning experiences. Conclusions: Based on previous theoretical modelling and practical examples we delineate two key principles of Affective Learning Design : (i) the design of emotion-laden learning experiences that effectively simulate the constraints of performance environments in sport; (ii) recognising individualised emotional and coordination tendencies that are associated with different periods of learning. Considering the role of affect in learning environments has clear implications for how sport psychologists, athletes and coaches might collaborate to enhance the acquisition of expertise in sport. Highlights: The role of emotion in the pursuit of expertise in sport has often been neglected. Performers should be immersed in learning environments that challenge and stimulate. Practitioners need to accurately simulate potential emotional and cognitive contexts. Principles of Affective Learning Design pose implications for developing sport expertise.